More insights into the interaction between age, exposure, and attitudes in language attrition and retention from the perspective of bilingual returnees - Matos, Joana (2022)
Aims and Objectives: The study investigates the effects of age, language use, and attitudes on Portuguese returnee bilinguals’ knowledge of German nominal morphology. We focused on language attrition. In addition, we compared whether the results of returnee bilinguals differ in relevant ways from the performance of L1 speakers of German and, if so, in which domains. Methodology: A background questionnaire and offline tasks that elicit lexical knowledge, case, gender, and plural marking in German were applied to a group of Portuguese–German bilingual returnees (N = 20) and a group of German L1 speakers (N = 20). Data and Analysis: The elicited data were analyzed through non-parametric tests (Mann–Whitney tests, Wilcoxon tests, and Spearman correlation tests), since not all the requirements for running mixed models could be fulfilled. Findings: The results show that bilingual returnees have very stable knowledge of the analyzed properties: parts of morphosyntactic knowledge are acquired and stabilized in childhood and remain highly invulnerable to loss of contact throughout the speakers’ lifetime. However, returnees’ knowledge of the German case system is constrained by age of input loss, language use, and attitudes. Ungrammatical plural marking is correlated with the speakers’ bonds to the German language and culture. No cross-linguistic influence from Portuguese was found in the domain of plural marking. Originality: This study resumes the question of differential attrition effects in returnee bilinguals by using a more controlled methodology. It extends the investigation to returnees’ performance in the lexical domain and with regard to case, gender, and number morphology in German, also quantifying other variables, such as the age of onset of bilingualism, the amount of contact with German after return, and the length of residence in Portugal. In addition, it focuses the less researched question regarding the role of the returnees’ attitudes toward both their languages. Significance/Implications: The study highlights the multi-dimensional factors that constrain language proficiency over a bilingual speaker’s lifetime.